Submicron Patterning Techniques for Perovskite Optoelectronics From Materials Challenges to Scalable Device Integration - Ahn, Dante; Lee, Minz; Jang, Youngsoo; Jung, Gun Young; Pak, Yusin (John Wiley and Sons Inc., 2026)
Halide perovskites are promising materials for future optoelectronic and display systems. They combine strong optical absorption, mechanical flexibility, low-cost solution processing, and tunable band structures. To serve emerging applications such as high-resolution AR/VR micro displays, optical logic gates, and neuromorphic vision processors, patterning methods should deliver sub-100 nm resolution, more than 99% photoluminescence retention in multilayer stacks, and alignment precision better than 500 nm. Sensitivity to polar solvents, heat, and chemical treatments limits compatibility with conventional photolithography and often leads to degradation during fabrication. This review surveys recent patterning strategies that address these issues. The discussion centers on four criteria: solvent compatibility, resolution, alignment accuracy, and process methodology. Mask-based approaches such as direct photolithography and mold-guided growth are compared with mask-free routes, including inkjet printing and laser-induced crystallization. Emerging directions include perovskite-compatible photoresists and hybrid schemes that couple nanoscale precision with wafer-scale scalability, outlining a path toward high-density, multifunctional, and vision-adaptive optoelectronic platforms.